Effect of Microbiota on Health and Disease - El-Sayed, Hoda (IntechOpen, 2022)
This book discusses the effect of microbiota on human health and disease. The microbiome is a complex collection of microorganisms. The microbial community differs across body sites, driven by different environmental conditions, immunological factors, and interactions between microbial species. It is now well known that the microbiome interacts with its host, assisting in the bioconversion of nutrients and detoxification, boosting immunity, and protecting against pathogenic microbes. This book addresses such topics as the pathogenesis and role of microbiota in disease, the relationship of the microbiome with obesity, the interactions of gut microbiota and the brain, and the development of functional foods fortified with probiotic microorganisms.